Temporal changes of cardiovascular risk factors in a town in Gujarat - S Peter; M Mashhadi; D J Ajith; H Wesley (Journal of Integrated Health Sciences)
Background: Modernization has also led to change in trivial health parameters which on aggregation culminate in transition of demography and epidemiology of disease pattern. Non-communicable diseases (NCDs) such as cardiovascular diseases (CVDs) have increased. 20 year trend comparison of CVD risk factors is depicted in this study. Methods: Two cross-sectional studies were conducted about 20 years apart. The former survey was conducted during 1991-94 and the latter during 2011-2013 period. Details on self-reported diabetes, daily physical activity and tobacco use were collected using a questionnaire. Blood pressure was measured using a sphygmomanometer in the baseline survey and Omron HEM 7111(1) automatic blood pressure monitor in the latter survey. Serum total cholesterol level was measured using a random blood sample. The trends of CVD risk factors were compared using percentages. Results: About 1882 and 2371 individuals were included in the former and latter study. Self-reported diabetes increased from 6% t0 19%. Tobacco use decreased from 52% to 20%. Sedentary physical activity decreased from 53% to 49%. Hypertension increased from 7% to 40%. Serum cholesterol above 255 mg/dl increased from 2% to 8%. Conclusion: Though the two studies were different in their blood pressure measurement instrument, sampling technique, population characteristics, and the fact that few risk factors were self-reported which could involve reporting bias; this crude comparison of CVD risk factors can be an eye opener to the medical fraternity.